Gender Budgeting in G7 Countries. (Policy Papers; Policy Paper ;, 2017)
At the request of the Italian Presidency of the G7, the IMF has prepared a paper on gender-budgeting as a contribution to the G7 initiative on equality. The paper provides an overview of gender-responsive budgeting concepts and practices in the G7 countries. It summarizes recent trends in gender equality in G7 and advanced countries, noting that while equality has improved overall, exceptions and gaps remain. Recognizing that many fiscal policies have gender-related implications, this paper: Sets out the main fiscal policy instruments, both expenditure and tax, that have a significant impact on gender equality. Provides a conceptual framework for the public financial management (PFM) institutions that play an enabling role in implementing gender-responsive fiscal policies. These instruments include gender budget statements, gender impact assessments, performance-related budget frameworks, and gender audits. Ministries of finance have an especially important role in promoting and coordinating gender budgeting, and associated analytical tools. Provides an assessment of the status of gender budgeting in the G7 countries. In preparing the paper, the IMF carried out a survey of PFM institutions and practices in the G7, as well as in three comparator countries that are relatively strong performers in developing gender-responsive budgeting (Austria, Belgium, and Spain). This information was complemented by other sources, including recent studies by the OECD and the World Bank. The main policy implications and conclusions of the paper include: Well-structured fiscal policies and sound PFM systems have the potential to contribute to gender equality, furthering the substantial progress already made by the G7 countries. While G7 countries have made effective use of a wide range of fiscal and non-fiscal policies to reduce gender inequalities, there has generally been less progress in developing effective gender-specific PFM institutions; embedding a gender dimension in the normal budgeting and policy-making routines varies across G7 countries and is not done systematically. Fiscal policy instruments of relevance to increasing gender equality include the use of tax and tax benefits to increase the supply of female labor, improved family benefits, subsidized child-care, other social benefits that increase the net return to women's work, and incentives for businesses to encourage the hiring of women.